Representation Of the Climate Crisis in The Lyrics of “Telan” by FSTVLST - Daffa Gilbran Amaranggana (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2025)
This study aimed to determine the message of the climate crisis in the lyrics of the song Telan by FSTVLST. The drastic changes in weather patterns, with the average world temperature increasing, accompanied by the emergence of extreme impacts such as floods, droughts, and rising sea levels, have attracted the world's attention. The community has felt issues related to the climate crisis, but the lack of awareness to reduce or prevent the occurrence of the climate crisis is still relatively passive. The song Telan tells about the conditions, especially in urban areas at this time, so that later it will provide us with awareness of how important it is to maintain the balance of nature. In conducting the study, the author used a descriptive qualitative method, using the Roland Barthes semiotic analysis approach using several main points, namely the meaning of denotation, connotation, and ideology in finding out the meaning of the message delivery in the form of social criticism in the FSTVLST song entitled Telan. It can be concluded that humans are the main cause of the climate crisis on earth with their actions that harm nature through the lyrics of the song Telan written by FSTVLST using metaphorical language. Keywords: Climate Crisis, FSTVLST, Semiotica, Song Lyric